Deficiencies and Inhibitors of Thromboplastic Activity - Grannis, G. F; Kazal, L. A (Thrombosis and Haemostasis, 1966)
The effects of hereditary deficiencies of thromboplastic proteins (hemophilia A and B) on the time course of thrombin appearance and disappearance in plasma (the thrombin activity curve, TAC) were compared with the effects of a naturally occurring gamma-globulin inhibitor of thromboplastic activity and with an anti-thromboplastic activity derived from cephalin (phosphatidylserine-lipoprotein complex).Both inhibitors inhibit reactions involving the protein in which hemophilia A plasma is deficient (factor VIII).